Meta-Earth: an extensible narrative-driven virtual earth visualization of the adverse effects of climate change in an immersive 3D virtual reality environment - Lee, Zhen Wei (Nanyang Technological University, 2022)
Virtual reality is a powerful platform to immerse users into environments that seem abstract and far away, and to also simulate the future. It advances a user’s understanding of the environment, by placing them directly in these foreign situations, thereby helping them to immediately have a better grasp of the situation and form strong memorable and emotional connections.